ARTIFICIAL INTELLIGENCE ADOPTION AND ITS IMPACT ON ACCOUNT-ING INFORMATION QUALITY AND ACCOUNTING PROCESS EFFICIENCY - Renna Magdalena; Oliandes Sondakh; Olivia Yasmin Pranadia Suyitno (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2026)
Digital transformation and the increasing adoption of Artificial Intelligence AI have reshaped accounting practices toward more automated and data-driven systems. However, their effectiveness in enhancing information quality and process efficiency in Indonesia still requires empirical examination. This study aims to examine the effect of Artificial Intelligence AI adoption on accounting information quality and accounting process efficiency, while considering the mediating role of accounting information quality. The research employs a quantitative approach using purposive sampling combined with snowball sampling, involving 125 respondents. The data are analyzed using Structural Equation Modeling based on Partial Least Squares SEM PLS to test the relationships among the research variables. This study is expected to provide both theoretical and practical contributions to the development of technology-based accounting information systems in Indonesia.